Jeden bohater trzech opowiadań I.A. Bunina - Kapinos, Elena (Studia Rossica Posnaniensia, 2011)
The paper of Yelena Kapinos One Protagonist of Three Short Stories by Ivan Bunin analyzes three short stories by Ivan Bunin (Grammar of Love, A Winter Dream and In a Never- Never Land). The stories are connected through the same recurring protagonist, Ivlev, who functions as a “mediator” between the world of the characters and that of the author. The three texts are structured as a kaleidoscope of similar motifs, details and narrative techniques that reveal the key elements of Bunin's poetic universe.